Rancang Bangun Biofilter untuk Pengolahan Limbah Cair Kegiatan Sentra Wisata Kuliner di Kecamatan Tambaksari, Kota Surabaya - Apri Yulianto; Arlini Radityaningrum; Ro’du Dhuha Afrianisa (Al-Ard: Jurnal Teknik Lingkungan, 2021)
The development of culinary business at Culinary Tourism Centre (CTC) has produced domestic wastewater from dish washing activities and food residues. One CTC in Tambaksari District, Surabaya City has not had Wastewater Treatment Plant (WWTP) yet. The CTC only has equalization tank for accommodating wastewater before discharged into the water body. This research aimed to determine the characteristics of domestic wastewater from the CTC and to design the appropriate WWTP in the CTC. The standard was based on the Regulation of the East Java Governor Number 72 Year 2013. The result showed that the concentrations of TSS, grease and oil, BOD, COD were 14 mg/L, 1.59 mg/L, 1154.8 mg/L, and 2054.8 mg/L, respectively. The WWTP units consisted of a grease trap, an equalization tank, primary sedimentation tank, anaerobic tank, aerobic tank, and secondary sedimentation tank. The estimated cost to build the WWTP was IDR 278,093,774.